Perspective towards atomic‐resolution imaging of two‐dimensional polymers. (1st June 2021) - Qi, Haoyuan; Liang, Baokun; Kaiser, Ute
Abstract: Recent years have witnessed the rise of an emerging class of synthetic two‐dimensional (2D) materials‐2D polymers. The combination of organic chemistry and rational design of polymeric crystals has stimulated tremendous research efforts in the controlled synthesis of 2D polymers. However, despite the advancement in synthetic methodologies, the structural characterization of 2D polymers remains a significant challenge. Although aberration‐corrected high‐resolution transmission electron microscopy (AC‐HRTEM) is capable of direct imaging of atomic structures with sub‐Ångström resolution, electron radiation damage poses a substantial limit on the achievable image resolution due to instant decomposition of the molecular framework. In this Perspective, we will briefly discuss radiation damage mitigation strategies, which may eventually result in AC‐HRTEM imaging of 2D polymers down to the atomic scale. Abstract : Although atomic‐resolution imaging is readily achievable on aberration‐corrected transmission electron microscopes, the direct imaging of organic crystals, such as, 2D polymers and covalent organic frameworks, remains a formidable task. The trouble‐maker, i.e., electron radiation damage, and strategies to mitigate its detrimental effects, will be discussed in this Perspective.